Integrasi teknologi informasi dalam manajemen strategis di sekolah dasar: Integration of information technology in strategic management at elementary schools - Iskandar, Nanang; Nugraha, Mulyawan Safwandy; Giu, Isra Yanuar (Risalah Kharisma, 2025)
This research addresses the significant gap in empirical studies concerning Information Technology implementation in Indonesian elementary schools' strategic management. The study aims to analyze implementation strategies, identify supporting and hindering factors, and develop an applicable IT governance model for elementary education contexts. Employing a qualitative case study methodology, data were collected through in-depth interviews, participatory observations, and document analysis at SD Al Azhar SBP, involving teachers, administrative staff, and school principals. Findings reveal exceptional technology adoption rates with 97% positive reception of the Notion platform, 91% parent satisfaction with digital enrollment systems, and 96.3% teacher confidence in technology utilization. However, a critical discovery emerged regarding 3.7% of teachers experiencing low digital self-efficacy, indicating a capability divide that extends beyond mere technological access. The research confirms the applicability of the Technology Acceptance Model while demonstrating its limitations in addressing organizational and cultural dimensions within elementary education environments. Consequently, this study proposes the School-Technology Integration Model (S-TIM), incorporating institutional readiness, pedagogical alignment, and community engagement as essential components for sustainable technology integration. The findings emphasize that successful digital transformation in elementary education necessitates comprehensive strategies addressing both technological infrastructure and human resource development through differentiated training programs and robust organizational support mechanisms.